Substance Use and the Number of Male Sexual Partners by African American and Puerto Rican Women - Jung Yeon Lee; Judith S. Brook; Kerstin Pahl; David W. Brook (Shahid Sadoughi University of Medical Sciences, 2017)
Background In the United States (US), there are 19 million new sexually transmitted disease (STD) infections each year. Untreated STDs can lead to serious long-term adverse health consequences, especially for young women. Centers for Disease Control and Prevention estimates that undiagnosed and untreated STDs cause at least 24,000 women in the US each year to become infertile. This clearly is a public health issue of great concern for young women. Methods The current cross-sectional study included a community sample consisting of 343 female participants (50% African Americans, 50% Puerto Ricans) at their mean age of 39 years. Regression analyses were conducted to examine the associations of time-varying factors within-person (e.g., substance use) and fixed effects factors between-persons (e.g., race/ethnicity) with the number of male sexual partners. Results: Alcohol use (b=0.14, p<0.01), cannabis use (b=1.10, p<0.01), marital status – unmarried (b=-0.16, p<0.05), and race/ethnicity – African American (b=-0.20, p<0.01) were significantly related to having a higher number of male sex partners in the past year. Conclusions: From a public health perspective, treatment and prevention programs for sexual risk behavior focused on substance use as well as socio-cultural factors (i.e., marital status, race/ethnicity) may be more effective than programs focused only on substance use.